2005
DOI: 10.1111/j.1600-079x.2005.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, stereological and radiological changes in pinealectomized chicken cervical vertebrae

Abstract: Considerable evidence supports the hypothesis that melatonin plays an important role in osteogenesis. We carried out an experiment to investigate histological and radiological changes in the cervical vertebrae of pinealectomized chickens. Thirty new-hatched chicks were divided into two groups: pinealectomized group (n=15) and nonpinealectomized control (n=15). Surgical pinealectomies were performed in Hybro broiler chickens at the age of 3 days. At 8 wk, one animal from each group was examined using computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…An extreme form of bone loss is seen, of course, in the clinical condition of osteoporosis in humans, in which bone loss is so severe that bone fractures occur without obvious trauma, or with ordinarily trivial trauma, and vertebral deformities (compression or collapse) do alter skeletal spinal integrity. Similarly, pinealectomized animals (salmon, chicken, mice) that have a relative melatonin deficiency also develop spinal curvature and bone demineralization not unlike that seen in osteoporosis in the human (13,24,26,39).…”
Section: Discussionmentioning
confidence: 94%
“…An extreme form of bone loss is seen, of course, in the clinical condition of osteoporosis in humans, in which bone loss is so severe that bone fractures occur without obvious trauma, or with ordinarily trivial trauma, and vertebral deformities (compression or collapse) do alter skeletal spinal integrity. Similarly, pinealectomized animals (salmon, chicken, mice) that have a relative melatonin deficiency also develop spinal curvature and bone demineralization not unlike that seen in osteoporosis in the human (13,24,26,39).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, there are some reports that melatonin controls the secretion of human growth hormone (Forsling et al 1999) and adrenocortical hormones (Kostoglou-Athanassiou et al 1998;Cagnacci et al 1995). Furthermore, it has been reported that melatonin enhances the diVerentiation of osteoblasts in vitro and promotes bone formation in vivo (Roth et al 1999;Koyama et al 2002;Turgut et al 2005;Machida et al 2006;Nakade et al 1999;Satomura et al 2007). These data strongly suggest that melatonin is involved in the development and/or growth of other hard tissues as well as bone tissue.…”
Section: Introductionmentioning
confidence: 80%
“…There are many previous studies showing that melatonin has a variety of physiological actions such as control of circadian rhythms (Redman et al 1983;McArthur et al 1997), regulation of body temperature (Dollins et al 1994), activation of the immune system (Garcia-Maurino et al 2000;Raghavendra et al 2001;Guerrero and Reiter 2002), anti-tumor activity (Hill and Blask 1988;Martínez-Campa et al 2006;Sánchez-Barceló et al 2005), function as a free radical scavenger and antioxidant (León et al 2005;Tan et al 2007) and anabolic eVects on bone formation (Roth et al 1999;Koyama et al 2002;Turgut et al 2005;Machida et al 2006;Nakade et al 1999;Satomura et al 2007). However, no data are available about its eVect on tooth development.…”
Section: Discussionmentioning
confidence: 96%
“…These facts and the above described effects of melatonin on bone physiology prompted studies on their possible utility as a complementary therapy for osteoporosis. Melatonin has been shown at the cell and tissue levels to promote osteogenesis and prevent bone deterioration in mammals [55], birds [56, 57], and fishes [21]. …”
Section: Melatonin and Osteoporosismentioning
confidence: 99%
“…In particular, the loss of melatonin induces a scoliotic curvature and reduces mean weight and length of cervical vertebrae, possibly due to a reduction in the total number of osteocytes. These results were interpreted to mean that melatonin may act to enhance osteocyte proliferation in the cervical vertebrae [57]. …”
Section: Melatonin and Adolescent Idiopathic Scoliosis (Ais)mentioning
confidence: 99%